TOWARD A PSYCHOLOGICAL THEORY OF BODY LANGUAGE - Sakvarelidze, Ramaz; Buachidze-Gabashvili, Manana (European Scientific Journal, ESJ, 2016)
The concept of the Language of Body is analyzed based on literature. The attempts of its theoretical explanation are discussed. The Psychology of Set (Uznadze) is considered as having potential for further research and better understanding of the phenomenon.